EXTH-31. COMBINATION OF TUMOR TREATING FIELDS (TTFIELDS) AND PACLITAXEL PRODUCES ADDITIVE REDUCTIONS IN PROLIFERATION AND CLONOGENICITY IN PATIENT-DERIVED METASTATIC NON-SMALL CELL LUNG CANCER (NSCLC) CELLS. (11th November 2019) - Michelhaugh, Sharon; Mittal, Sandeep
Abstract: Clinical trials are underway to test the efficacy of TTFields in patients with progressive NSCLC or NSCLC brain metastases following standard-of-care or radiosurgery, respectively. Our study utilized patient-derived cells isolated from NSCLC brain metastases from a patient previously treated with standard-of-care chemo-radiation prior to progression to brain metastasis. These patient-derived cells underwent TTFields application in vitro with and without paclitaxel to determine if the response to the combination of TTFields with paclitaxel would be different from either treatment alone. Use of patient tissues was approved by the Institutional Review Board. Written informed consent was obtained from the patient, who was 60 years-old and female. She received concurrent carboplatin/paclitaxel and radiotherapy to the upper lobe of her left lung prior to discovery and resection of a solitary brain lesion. Cells isolated from the metastatic brain tumor were cultured for 3 passages prior to plating on coverslips (4×10 4 each) in DMEM/F12 media with 10% fetal bovine serum. TTFields were applied at ~1.6 V/cm at 150 kHz. Paclitaxel was added to the media to a final concentration of 5 nM. After 14 days, cell lysates were assayed for lactase dehydrogenase (LDH) to represent cell number (n=5) or were harvested and replated in triplicate for the clonogenic assay (n=3). Groups were compared with one-way ANOVA. Mean ± SD of LDH for the control, TTFields-alone, paclitaxel-alone, and the combination were 1.83 ± 0.09, 1.34 ± 0.15, 0.81 ± 0.04, and 0.46 ± 0.21, respectively (ANOVA p< 0.0001). Clonogenic assay counts for the same groups were 26641 ± 4625, 17399 ± 5998, 8697 ± 1617, and 1598 ± 598 (ANOVA p= 0.0003). The additive effects of TTFields and paclitaxel suggest that they target different cell populations within a heterogeneous tumor, and that patients previously treated with standard-of-care may benefit from TTFields therapy.